The theology of the book of Jeremiah - Brueggemann, Walter (Old Testament theology., 2007)
The Book of Jeremiah, second of the three major prophets, is immensely complex. Its different interpretive voices stretch across several generations and do not cohere into an easily identifiable and uniform theology. Instead, in both poetry and prose, the Book of Jeremiah witnesses an ongoing conversation among different advocates concerning the crisis of Babylon's expansion and Jerusalem's demise. In this volume, Walter Brueggemann elucidates these various voices in the context of Judah's commitment to the rule of the one God, Yhwh. This messy interface of the theological and political constitutes the primal challenge of the Book of Jeremiah, and Brueggemann shows how the book asserts that God continues to be similarly and disturbingly operative in the affairs of the world. In this way, contemporary crises such as American imperialism and religiously inspired terrorism are shown to be dislocations with ancient antecedents, but dislocations that continue to invite readers to new futures that combine divine agency and human inventiveness rooted in faithfulness. --From publisher's description.